Large‐scale insertional mutagenesis of Chlamydomonas supports phylogenomic functional prediction of photosynthetic genes and analysis of classical acetate‐requiring mutants. (April 2015) - Dent, Rachel M.; Sharifi, Marina N.; Malnoë, Alizée; Haglund, Cat; Calderon, Robert H.; Wakao, Setsuko; Niyogi, Krishna K.
Summary Chlamydomonas reinhardtii is a unicellular green alga that is a key model organism in the study of photosynthesis and oxidative stress. Here we describe the large‐scale generation of a population of insertional mutants that have been screened for phenotypes related to photosynthesis and the isolation of 459 flanking sequence tags from 439 mutants. Recent phylogenomic analysis has identified a core set of genes, named GreenCut2, that are conserved in green algae and plants. Many of these genes are likely to be central to the process of photosynthesis, and they are over‐represented by sixfold among the screened insertional mutants, with insertion events isolated in or adjacent to 68 of 597 GreenCut2 genes. This enrichment thus provides experimental support for functional assignments based on previous bioinformatic analysis. To illustrate one of the uses of the population, a candidate gene approach based on genome position of the flanking sequence of the insertional mutant CAL027_01_20 was used to identify the molecular basis of the classical C. reinhardtii mutation ac17. These mutations were shown to affect the gene PDH2, which encodes a subunit of the plastid pyruvate dehydrogenase complex. The mutants and associated flanking sequence data described here are publicly available to the research community, and they represent one of the largest phenotyped collections of algal insertional mutants to date.